Diseminasi UMB Berbasis Limbah Tembakau dengan Teknologi Hidraulik Press di Kelompok Ternak Agrapana Sejahtera - Andriani, Mira; Syahniar, Theo Mahiseta; Nurkholis, Nurkholis; Kustiawan, Erfan; Lestari, Datik (P3M Politeknik Negeri Jember, 2025)
Urea Molasses Block (UMB) is an animal feed supplement that contains micro nutrients which function to improve feed digestibility, provide energy and increase appetite. Based on research results, giving 5% tobacco waste is able to eradicate worms in livestock. Worms are parasites in the digestive tract of livestock. Infected livestock will usually be disturbed in the digestive process, so that in the end it will have an impact on performance in the form of low body weight gain. In general, making UMB is still done manually and traditionally, partners also have not yet got the right formula for making it, which has an impact on the performance of beef cattle. in the Agrapana Sejahtera livestock group. The dissemination of making UMB based on tobacco waste using hydraulic press technology aims to enable farmers who are members of group partners to be able to independently make UMB based on tobacco waste using hydraulic press technology to facilitate and apply the making of UMB to provide supplements that can improve the performance of beef cattle. The output of this activity is an increase in farmers' understanding of producing UMB for the success of beef cattle, increasing knowledge and skills in processing tobacco waste-based feed using hydraulic press technology, and improving the performance of beef cattle.